The using of emulgators in the composition of complex food additives in the technology of meat products - Strashynskyi, Igor; Marynin, Andriy; Omelchenko, Maksym (My University, 2021)
Currently, in conditions of decreasing in the resources of raw meat materials, the using of raw materials of non-standard quality (for example, frozen meat with a long storage period, with a high content of fat and connective tissue, meat with signs of PSE, RSE and DFD), manufacturers are forced not only to constantly maintain the quality of their products, but also to ensure a reduction in its cost. В даний час в умовах зменшення ресурсів м'ясної сировини широко поширене використання сировини нестандартної якості (наприклад, заморожене м'ясо тривалого зберігання, з підвищеним вмістом жиру і сполучної тканини, м'ясо з ознаками PSE, RSE і DFD), виробники змушені не тільки постійно підтримувати якість своєї продукції, але й забезпечувати зниження її собівартості.
Keywords: кафедра технології м’яса і м’ясних продуктів; long-term frozen meat; emulgators; complex food additives; емульгатори; харчові добавки